Stakeholders' Perceptions About a Newly Established Dental School with a Problem‐Based, Student‐Led, Patient‐Centered Curriculum: A Qualitative Study. Issue 3 (1st March 2016) - Ali, Kamran; Tredwin, Christopher; Kay, Elizabeth; Slade, Anita
Abstract : The aim of this study was to explore the perceptions of stakeholders regarding a newly established dental school with a problem‐based, student‐led, patient‐centered curriculum in a community setting. Qualitative methods using 16 semistructured interviews and two focus groups were used to engage a range of stakeholders from students to faculty members to practitioners. Purposive sampling was employed with participants contacted through professional channels. Interview and focus group transcripts were transcribed verbatim. The data were analyzed thematically using an inductive approach. Themes related to preparedness of dental graduates were identified during data analyses. Early clinical exposure with patients in the first year of the course, holistic care using a patient‐centered approach, and the acquisition of communication skills, professionalism, team‐working skills, reflective practice, and evidence‐informed clinical practice were perceived to be key strengths of the curriculum. The participants also expressed the need to strengthen teaching of life sciences and provide additional clinical experience in simulated general dental practice clinics. This study provides insight into the perceptions of a wide range of stakeholders and provides a deeper understanding of the merits and challenges of an innovative undergraduate dental curriculum.